Distinct IgE sensitization profiles in chronic urticaria: a comparative study with classic allergic diseases - Yang, Xianjie; Li, Shifei; Chen, Anqi; Wang, Huan; Deng, Sisi; Ni, Bing; Song, Zhiqiang; Chen, Qiquan (Frontiers in Immunology, 2024)
IntroductionChronic urticaria (CU) is not traditionally classified as an allergic disease, but emerging evidence suggests a link to atopy. The quintessential marker of atopy is IgE sensitization, there is scarce information on the IgE sensitization characteristics of CU.MethodsTo investigate IgE sensitization characteristics in CU, and compare them with classic allergic diseases. We retrospectively analyzed the results of specific IgE (sIgE) and total IgE (tIgE) in CU patients, explored the distribution patterns of these atopic markers in CU, and compared these data with those of atopic dermatitis (AD), allergic rhinitis (AR), asthma (AS), and healthy controls (HC).Results1149 patients (396 CU, 411 AD, 101 AR, 139 AS and 102 HC) were included in the study. 33.1% of CU patients showed positive sIgE and 49.0 % had elevated tIgE levels, significantly higher than those in HC. Comparative analysis with classic allergic diseases showed CU patients had a lower sIgE positivity rate but no significant difference in tIgE levels. Gender and age influenced sensitization profiles, with male CU patients showing a higher sIgE positivity rate. The distribution of sIgE levels, allergen categories, and tIgE elevated levels range in CU differed from classic allergic disease. The concordance rate between sIgE and tIgE results in CU was lower than in classic allergic disease.ConclusionOur study reveals that a significant proportion of CU patients display IgE sensitization, suggesting a clear atopic background compared to the general population. However, the IgE sensitization profile in CU differs from that of classical allergic diseases such as AD, AR, and AS, characterized by relatively lower intensity of IgE sensitization. The underlying reasons for this phenomenon and its clinical implications in CU warrant further research.